Role of Green Finance in Attaining Corporate CSR Goals - Kamran, Muhammad Rizwan; Ambreen, Sadaf; Kiran, Faiqa; Mumtaz, Raheel (Pakistan Journal of Humanities and Social Sciences, 2022)
To achieve sustainable development goals, economies are increasingly adopting a green financing strategy. Socioeconomic and environmental initiatives are required for the long-term growth of the firm. CSR developed as a strategy to foster social harmony via the sustained prosperity of corporations. However, in order for organizations to remain consistent with their CSR and sustainability objectives, enormous resources are required. This study explores how green finance contributes to accomplishing, succeeding at, and strengthening CSR in the banking sector. Primary information was gathered from 320 workers in the Pakistani banking sector in order to establish the relationship between the variables used in this study. Green financing and its environmental, economic, and social considerations contribute to the improvement of CSR's numerous aspects, as shown by survey data. The results demonstrated a positive relationship between green finance dimensions and CSR goals. Based on these findings, the researcher concludes the hat financial services industry should put more resources into cultivating CSR behaviours.